SAE Technical Paper Series 2007
DOI: 10.4271/2007-01-1170
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Neck Injuries in Children Involved in Frontal Collisions

Abstract: There is a paucity of data regarding the potential for pediatric cervical spine injury as a result of acceleration of the head with no direct impact during automotive crashes. Sled tests were conducted using a 3-year-old anthropomorphic test device (ATD) to investigate the effect of restraint type and crash severity on the risk of pediatric inertial neck injury. At higher crash severities, the ATD restrained by only the vehicle three-point restraints sustained higher peak neck tension, peak neck extension and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Biomechanical computer modeling has also concluded that a child's neck would break at forces lower than those required to produce the intracranial injuries associated with SBS [3,35]. Cadaveric studies have quantified the mechanical properties and strength of the human infant neck [17,31,34], supporting the supposition that structural neck failure would result from even the accelerations reported during shaking of the Aprica 3.4 [28].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical computer modeling has also concluded that a child's neck would break at forces lower than those required to produce the intracranial injuries associated with SBS [3,35]. Cadaveric studies have quantified the mechanical properties and strength of the human infant neck [17,31,34], supporting the supposition that structural neck failure would result from even the accelerations reported during shaking of the Aprica 3.4 [28].…”
Section: Introductionmentioning
confidence: 99%